2014
DOI: 10.1183/09031936.00121514
|View full text |Cite
|
Sign up to set email alerts
|

Should use of 4 hours continuous positive airway pressure per night be considered acceptable compliance?

Abstract: @ERSpublications CPAP use can determine the cardiovascular risk reduction; physicians must endeavour to get the best CPAP use http://ow.ly/zPZbP Continuous positive airway pressure (CPAP) reduces blood pressure in obstructive sleep apnoea (OSA) patients, as well as in patients with resistant hypertension. The effect of CPAP is directly related to treatment compliance [1][2][3]. Observational studies have shown a reduction in cardiovascular mortality risk in severe OSA patients treated with CPAP and adequate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
(29 reference statements)
0
11
0
2
Order By: Relevance
“…Suggesting that downloading ventilator data to assist in modifying NIV prescriptions is a useful adjunct to improve patient comfort and achieve a clinically meaningful increase in NIV compliance. Data from Masa et al 23 and Borel et al 24 suggest greater gains the longer NIV is used; thus a 2-hour increase in NIV use could result in greater patient benefit. Furthermore, the small sample size and heterogeneity of the population in this study may have resulted in a statistical underestimation of the changes observed in NIV compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting that downloading ventilator data to assist in modifying NIV prescriptions is a useful adjunct to improve patient comfort and achieve a clinically meaningful increase in NIV compliance. Data from Masa et al 23 and Borel et al 24 suggest greater gains the longer NIV is used; thus a 2-hour increase in NIV use could result in greater patient benefit. Furthermore, the small sample size and heterogeneity of the population in this study may have resulted in a statistical underestimation of the changes observed in NIV compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Von einer PAP-Intoleranz sprechen wir demnach, wenn die Therapie bei initial bestehender Motivation eingeleitet wurde, jedoch aus den oben genannten Gründen ungenügend genutzt wird. Entscheidendes quantitatives Kriterium für eine PAP-Intoleranz ist eine durchschnittliche Nutzung von weniger als 4 h pro Nacht über einen längeren Zeitraum [6,8]. Die Nutzung/Nichtnutzung sollte durch einen objektiven Nachweis (z.…”
Section: Pap-intoleranzunclassified
“…A commonly held view is that a patient should use their CPAP device for at least 4 hours per night to experience an improvement of sleepiness and daily functioning. [13][14][15][16][17][18] However, a considerable proportion of CPAP users fail to achieve this threshold. Accordingly, 46-83% of the patients on CPAP could be described as insufficiently treated, if optimal adherence were defined as >4 hours of nightly use.…”
Section: Introductionmentioning
confidence: 99%